2009
DOI: 10.1016/j.freeradbiomed.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative epithelial host defense is regulated by infectious and inflammatory stimuli

Abstract: Epithelia express oxidative anti-microbial protection that uses lactoperoxidase (LPO), hydrogen peroxide (H 2 O 2 ) and thiocyanate to generate the reactive hypothiocyanite. Duox1 and Duox2, found in epithelia, are hypothesized to provide H 2 O 2 for use by the LPO. To investigate regulation of oxidative LPO-mediated host defense by bacterial and inflammatory stimuli, LPO and Duox mRNA were followed in differentiated primary human airway epithelial cells, challenged with Pseudomonas aeruginosa flagellin or IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 35 publications
3
71
1
Order By: Relevance
“…In our setting, the H 2 O 2 /LPO system is unlikely to have a role based on the following observations. First, LPO is not secreted from in vitro cultured AECs [44] and all the studies that previously demonstrated an LPO-dependent antimicrobial function required the addition of LPO in the experiments [38,39,43]. However, here we observe an antiviral effect of DUOX2 without the ectopic addition of LPO.…”
Section: Rsv Interferes With the Expression Of Duox2contrasting
confidence: 44%
See 1 more Smart Citation
“…In our setting, the H 2 O 2 /LPO system is unlikely to have a role based on the following observations. First, LPO is not secreted from in vitro cultured AECs [44] and all the studies that previously demonstrated an LPO-dependent antimicrobial function required the addition of LPO in the experiments [38,39,43]. However, here we observe an antiviral effect of DUOX2 without the ectopic addition of LPO.…”
Section: Rsv Interferes With the Expression Of Duox2contrasting
confidence: 44%
“…To date, studies based on the use of antioxidant enzymes support the necessity of H 2 O 2 in the LPOdependent antibacterial defense [38]. Further studies suggest that DUOX2 is a source of H 2 O 2 production in the airways [39,40]. However, none of these studies have clearly demonstrated a functional connection between DUOX2-mediated H 2 O 2 production and LPO-dependent airway antibacterial defenses.…”
Section: Rsv Interferes With the Expression Of Duox2mentioning
confidence: 99%
“…We previously showed that IFN-g-stimulated NHBE cells cultured at the ALI produced high levels of H 2 O 2 , at up to 5-10 mM in apical washes used for assay (10). Thus, much higher concentrations exist in the ASL before washes were used to collect samples (dilution (23), corresponding to a surface volume of approximately 6 ml, because of the meniscus at the edge of the culture surface (24).…”
Section: Results H 2 O 2 Accumulates In Aslmentioning
confidence: 99%
“…Duox1 and Duox2 are regulated by cytokines (10-12) and bacterial products (10,13,14) to increase H 2 O 2 synthesis to high levels (10). Stimulation with interferon-g increased H 2 O 2 synthesis levels 30-fold when measured in air-liquid interface (ALI) cultures of normal human airway epithelial cells (10), leading to 10 mM H 2 O 2 in washes used for assays.…”
mentioning
confidence: 99%
“…Epithelial H 2 O 2 production, presumably by DUOX2, is thought to aid in direct oxidative microbial killing in association with secreted lactoperoxidase (3,4), and the prominent induction of DUOX2 in response to microbial and viral stimuli further supports its role in host defense (5,6). Studies of Drosophila and zebrafish have established the importance of their single DUOX gene in the maintenance of gut immunity (7)(8)(9), and analogous host-defense properties have been demonstrated for DUOX2 in the mammalian gastrointestinal tract (10,11).…”
mentioning
confidence: 92%